Chemical composition, antioxidant activity and development of a facial serum formulation from the extract of Hancornia speciosa - Panontin, Juliane Farinelli; Barbosa, Robson dos Santos; Isaac, Vera [UNESP]; Seibert, Carla Simone; Scapin, Elisandra (My University, 2022)
The goal of this work was to chemically characterise Hancornia speciosa extracts to develop an antioxidant serum formulation. Stem and bark extracts were prepared using 70% hydroethanol solution by Sohxlet and ultrasound assisted extraction. The content of total phenols, flavonoids, and antioxidant activity were evaluated, and chemical characterization was performed by HPLC -detector UV-VIS (SPD − 10 A). The formulation was developed with stem extract (0.250 mg/g) in hydroxyethylcellulose fluid gel. Stem extracts had higher total phenols and flavonoids, and higher antioxidant activity than bark extracts. The formulation presented low viscosity, a yellowish colour, 81.28% ± 0.14 of antioxidant activity. In the stability test, the physicochemical characteristics showed small variations, remaining more stable at a temperature of 5 °C, with an antioxidant activity of 64.81% ± 0.75. Therefore, the stem of H. speciosa has the potential to be used in antioxidant formulations.
Keywords: anti-ageing; DPPH; Mangabeira; phenolic compounds; phytocosmetics